Peningkatan Partisipasi Masyarakat Dalam Pengembangan Pariwisata Berbasis Tenun Bima Di Kelurahan Ntobo Kota Bima - Agrippina Wiraningtyas; Wahyuni Wahyuni; Anita Rahmawati; Syarifuddin Syarifuddin; Zulkifli Zulkifli (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2024)
Community-based tourism development has been recognised as a strategic approach to improving the welfare of local communities, especially in areas that have cultural wealth such as Ntobo Village, Bima City. Bima weaving, which is a traditional cultural product with deep historical and aesthetic values, has great potential to be developed as a tourist attraction. However, low community participation in the tourism development process is one of the main obstacles. This study aims to increase community participation in the development of weaving-based tourism in Ntobo Village and identify factors that influence the level of participation. The approach used is the Participatory Action Approach (PAA), which involves the community actively in every stage of the activity, from potential mapping, planning, to programme implementation and evaluation. The results showed a significant increase in community knowledge and involvement after various activities were implemented, such as seminars, training, and partnerships with related parties. In addition, the integration of sustainability principles in the development of weaving-based tourism products increased tourist attraction and helped preserve local cultural heritage. The programme also succeeded in strengthening cooperation between the community, local government, and business actors, thus supporting the sustainability of tourism development. In conclusion, active community participation is the key to success in the development of weaving-based tourism that can improve economic welfare while preserving local culture in Ntobo Village.